The Effectiveness of Playing Based Learning (PBBK) Model for Developing Kindness Character in Early Childhood - Kurniati, Euis (Indonesian Journal of Early Childhood Education Studies, 2015)
This study focused on the effectiveness of the PBBK model for developing kindness character in early childhood. The method in this research is pre experiments, with designd one-group pretest-posttest design. The research conducted in TK Labschool UPI. Sample used by 16 students who are at group A. Decision-makingis donein two ways, namelybycomparing thet valuet tableorby comparing theprobabilityvaluesobtainedwithÃŽÂ±=0.05. The results showed ofa paired t test(paired sample t test) of datapretest and posttestoverall kindness character student issignificantbecause ithas avalue of p<0.05. This meansthatthere aresignificantdifferences inthe kindness character beforeandafterthe application ofthe PBBK model orin other words the PBBK model is effective for developing kindness character in TK LabschoolUPI. Averagekindness characterbeforeapplication ofthe PKBB model amounted to16.133andthe averageincreased to19.733afterthe application ofthe PKBB model. Recommendations from this study is that this model more broadly validated by involving more schools to pilot the PBBK model.How to citeKurniati, E. (2015). The Effectiveness of Playing Based Learning (PBBK) Model for Developing Kindness Character in Early Childhood. Indonesian Journal of Early Childhood Education Studies, 4(2), 64-69. doi:10.15294/ijeces.v4i2.9457DOI 10.15294/ijeces.v4i2.9457